Connecting personal and community memory-making: Facebook Groups as emergent community archives - Gibbons, Leisa (UNIV SHEFFIELD DEPT INFORMATION STUDIES, 2019)
Introduction: Facebook groups provide spaces for 'emergent community archives' where individuals document and share community memory and identity. This paper asks what stories are being told about personal and community memory-making by the existence of these emergent community archives? Method: Criteria identifying emergent community archives was applied in search for Facebook groups related to Western Australia. In total, twenty-seven groups were found, fourteen public and thirteen closed. Analysis: The Facebook groups were analysed using narrative analysis techniques that ask questions about how, where, and to whom the story is told, what types of stories are being told, what patterns or features do the stories have, and what larger discourses or narratives are being encountered or communicated. Results: Activities in Facebook groups show a patterning around how stories are told. Choices made about how to represent a group identity and memory are generally limited due to the functionality of Facebook platform. Overall, the primary story being told concerns Facebook's control over memory-making and how the Group system promotes a fragmented community memory. Conclusions: Fragmented memories do not allow or provide a sense of how long people expect the groups to exist or what role they might play over time. The second stage research will ask Facebook Group administrators their reasons, expectations and requirements for community memory-making.